Biocrete : a microbial concrete - Tan, Annabel. (2012)
Concrete is the most commonly used building material due to its relatively low cost, compressive strength and durability. However, it has very low resistance to tension and is prone to brittleness. Hence, an alternative would be the use of engineered cementitious composites (ECC), which produce very fine crack width as compared to normal concrete. Yet, ECC has a high porosity and air content (voids) and hence has poorer transport properties than normal concrete. Therefore, one way to improve the transport properties is the application of calcite-forming bacteria on the surface of the concrete known as biodeposition. The use of calcite-forming bacteria has been widely studied in improving the strength and durability of concrete only, but application on ECC is a new area that has not been explored; and hence the need for this study. The process involves precipitation of calcium carbonate on concrete surface. Based on past research, Bacillus subtilis and Bacillus pasteurii were the bacteria selected for the study. These bacteria yield the highest amount of calcite and were also able to survive high alkaline conditions. The study involved three groups of concrete specimens, namely cement paste, untreated ECC and bacterially-treated ECC. These three groups of concrete specimens were first prepared and bacteria were cultivated to the desired concentration range. Biodeposition was then conducted by applying the bacteria on the newly casted cement paste and ECC specimens. Standard transport properties tests such as absorption and sorptivity were run on the specimens. The experimental results showed that the untreated ECC had a higher rate of absorption (sorptivity) than cement paste specimens, which could be due to higher number of voids and pores in the former. This supported the fact that untreated ECC had poorer transport properties. In addition, the percentage and rate of absorption of bacterially-treated ECC were found to be lower than untreated ECC specimens. This could be due to the formation of calcite by the bacteria on the surface of the specimens, thereby reducing the number of pores and voids. The results have shown that the application of calcite-forming bacteria had reduced the absorption percentage and sorptivity of ECC, and hence significantly improved the transport properties of ECC. In conclusion, the project was a success as the objective had been achieved. Future tests were recommended to include different types of bacteria genus other than Bacillus genus. Biocementation could also be explored and this could comprise the application of calcite-forming bacteria on recycled coarse aggregates (RCA).